Inhibitory Effect of L-Canavanine and L-Lysine on Arginase Activity in Sheep Spleen Tissue - Kandemir, Fatih Mehmet; Kaymaz, Mustafa Bahadir; Ozdemir, Necmi (Kafkas Univ, Veteriner Fakultesi Dergisi, 2014)
Arginase (L-arginine amidinohydrolase; (E.C.3.5.3.1) is the last enzyme of urea cycle and it catalyzes the hydrolysis of L-arginine to urea and L-ornithine in livers of animals. It helps to the excretion process of urea from the body, which is the most soluble and non-toxic form of nitrogen. Along with its essential role in urea synthesis, arginase is also found to have important roles in ornithine production for polyamine, proline and glutamate synthesis and in immune system activation. Mostly found in liver tissue, arginase enzyme is also found in non-ureolytic tissues like heart, rumen, skeletal muscle, kidney, intestine, brain, spleen, thyroid gland, salivary gland, erythrocyte, fibroblast, macrophage, mammary gland in lactation, testicle. With this study, it was aimed to assess the inhibitory effects of arginase in sheep spleen tissue on L-canavanine and L-lysine. Consequently, it was observed that L-lysine as a L-amino acid and guanidine compound L-canavanine inhibits enzyme activity non-competitively.
L-kanavanin ve l-lizin’in koyun dalak doku arginaz aktivitesi Üzerine İnhibisyon etkisi
Keywords: Arginase; L-lysine; L-canavanine; Sheep spleen tissue